Práctica de valores como estrategia de transformación de la convivencia escolar y la formación de gestores de paz (2018)
Coexistence is the ability of people to live with others (live-in) in a framework of reciprocal respect and solidarity, a good coexistence promotes the values, norms and attitudes of people, based on this concept the present project studies a problem presented at the Brooks Hill Bilingual School Educational Institution, there are conflicts and problems of school coexistence in boys and girls; specifically in grades 6 and 7, due to the factors of extra-age, because of the social life system in which they operate. Their behavior is affecting in them the curricular learning, the lack of tolerance and respect in the classroom, causing demotivation, lack of interest in the development of the classes, by the little capacity of concentration, originated by the disorder and noise caused by the constant fights, which leads to low student performance, resulting in school dropout or loss of the school year. Through this research, the impact of the strategy of values practice in the improvement processes of school coexistence and the formation of Peace Managers, in grades 6 and 7 of the Brooks Hill Educational Institution, was analyzed. Manifestations of school coexistence, a pedagogical strategy was formulated based on extracurricular activities of values practice for the transformation of school coexistence and the formation of peace managers and the impact of the development of extracurricular activities based on the practice of values for the transformation of school coexistence and the training of peace managers